Contrafacta. Modes of music re-textualization in the late sixteenth and seventeenth century, eds. Marina Toffetti, Gabriele Taschetti, Kraków 2020 - Ferrari, Nicolò (Muzyka, 2021)
Recenzja książki: Contrafacta. Modes of music re-textualization in the late sixteenth and seventeenth century, red. Marina Toffetti, Gabriele Taschetti, Kraków 2020